Lung cancer imaging - Ravenel, James G. (Contemporary Medical Imaging, 2013)
Lung Cancer Imaging provides a clinically focused guide to the diagnosis, staging, and management of lung cancer.  It incorporates a multi-disciplinary approach to the understanding of the causes of lung cancer and treatment of this disorder.  This book presents the epidemiology and classification of lung cancer; screening protocols; imaging in non-small cell lung cancer; preoperative evaluation for lung cancer resection; staging and imaging of small cell carcinoma; surgical treatment for non-small cell lung cancer; the use of radiotherapy in lung cancer; and imaging following lung cancer treatment. With contributions from a distinguished group of thoracic oncology specialists, it is an authoritative resource for radiologists, oncologists, pulmonologists, and thoracic surgeons.     Foreword by Mark Green, MD, Professor of Medicine, Emeritus, Medical University of South Carolina.